The Role of Teachers in Instilling Student Discipline in 2013 Curriculum Based Learning - Purnomo, Agus (Program Magister Teknologi Pendidikan Universitas Jambi, 2020)
This research aims to determine the role of teachers in planting student discipline in learning the 2013 curriculum for class IVC at elementary school 112/1 Perumnas. The aspect studied is the teacher's efforts to instill values discipline for students at elementary school 112/1 Perumnas. This research uses a qualitative approach. The subject of this research is the principal and class IVC teacher. Data collection was carried out through observation, interviews and documentation. Data analysis techniques used is data reduction, displaying data and drawing conclusions. Researcher using triangulation techniques to obtain data validity. The results of this research indicate that the teacher's role is in improving student discipline has been implemented quite well, instilled discipline carried out by teachers through making rules, teaching habits, giving punishment, giving rewards, and setting an example. Based on the research results, it can be concluded that the teacher has instilling the value of discipline at elementary school 112/1 Perumnas. the planting includes; (1) elements of discipline; (2) teachers combine approaches authoritarian and democratic, (3) schools involve the school committee and parents in applying discipline, (4) steps in implementing discipline not yet implemented by all teachers.